The complex journey of the laryngeal cancer patient: from attempted organ-preserving treatment, to the need for a reconstructive stage to restore lost functions - A. P. Polyakov; M. V. Ratushnyy; I. V. Novikova; A. M. Svirnovskaya (Опухоли головы и шеи)
Laryngeal cancer occupies the leading place among malignant tumors of the ENT organs. The main approach to the treatment of advanced forms of this disease remains laryngectomy, leading to the loss of vocal function and reduced quality of life of patients.The article presents the possibilities of modern methods of reconstructive surgery aimed at restoration of the lost functions after laryngectomy. A clinical case of successful restoration of swallowing and speech functions in a patient who after organ preservation treatment and recurrence underwent laryngectomy with subsequent reconstruction of the pharynx with a free jejunal flap is described. Thus, pharyngeal reconstruction with free jejunal flap is an effective method of social rehabilitation of patients after laryngectomy, especially when organ preserving approaches are ineffective.